PERANCANGAN ARSITEKTUR ENTERPRISE MENGGUNAKAN FRAMEWORK TOGAF ADM 9.1 DAN COBIT 4.1 - Sofia Umaroh; Nur Fitrianti; Muhammad Iqbal (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
The use of Information Technology is very important The use of information technology is very important for higher education institutions to achieve business goals and provide good facilities for academic activities. The existing system at the university has its own system character shape, to find out whether the existing system is running as expected, it is necessary to measure the level of maturity. In integrating a good system, a framework is needed to measure the maturity level of Information Technology. In this research, architectural design was carried out using the Control Objectives for Information and Related Technology (COBIT) 4.1 framework with the domain used, namely PO2 and PO3. The first stage carried out in this study was to measure the maturity of Information Technology using COBIT 4.1 by distributing questionnaires based on statements in the domain used, namely PO2 and PO3. Then do the calculation of values ??from non-existent scale (level 0) to optimized (level 5) and have a picture of the expected conditions in the future. The measurement results of Information Technology Maturity at PO2 obtained a value of 2.35 where the condition is level 2 or repeatable and 2.59 at PO3 the condition is level 3 or defined. Based on these conditions, it can be used as a reference that the existing system in u has been running as expected but needs to be developed regularly